Three-dimensional visualization of cleared human pancreas cancer reveals that sustained epithelial-to-mesenchymal transition is not required for venous invasion - Hong, Seung-Mo; Jung, DongJun; Kiemen, Ashley; Gaida, Matthias; Yoshizawa, Tadashi; Braxton, Alicia M.; Noë, Michaël; Lionheart, Gemma; Oshima, Kiyoko; Thompson, Elizabeth D.; Burkhart, Richard; Wu, Pei-Hsun; et al. (Modern pathology, 2020)
Venous invasion is three times more common in pancreatic cancer than it is in other major cancers of the gastrointestinal tract, and venous invasion may explain why pancreatic cancer is so deadly. To characterize the patterns of venous invasion in pancreatic cancer, 52 thick slabs (up to 5 mm) of tissue were harvested from 52 surgically resected human ductal adenocarcinomas, cleared with a modified iDISCO method, and labeled with fluorescent-conjugated antibodies to cytokeratin 19, desmin, CD31, p53 and/or e-cadherin. Labeled three-dimensional (3D) pancreas cancer tissues were visualized with confocal laser scanning or light sheet microscopy. Multiple foci of venous and even arterial invasion were visualized. Venous invasion was detected more often in 3D (88%, 30/34 cases) than in conventional 2D slide evaluation (75%, 25/34 cases, P < 0.001). 3D visualization revealed pancreatic cancer cells crossing the walls of veins at multiple points, often at points where preexisting capillary structures bridge the blood vessels. The neoplastic cells often retained a ductal morphology (cohesive cells forming tubes) as they progressed from a stromal to intravenous location. Although immunolabeling with antibodies to e-cadherin revealed focal loss of expression at the leading edges of the cancers, the neoplastic cells within veins expressed e-cadherin and formed well-oriented glands. We conclude that venous invasion is almost universal in pancreatic cancer, suggesting that even surgically resectable PDAC has access to the venous spaces and thus the ability to disseminate widely. Furthermore, we observe that sustained epithelial-mesenchymal transition is not required for venous invasion in pancreatic cancer.
Published online: 7 November 2019
Gesehen am 21.04.2020